Implementation of Jean Watson’s Caring Theory In NICU Nursing Practice for Families of Low Birth Weight Infants (LBW) - Erni Handayani; Blacius Dedi; Tri Ismu Pujianto (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The increase in infant mortality rates is largely attributed to cases of low birth weight (LBW). This is supported by the high incidence of LBW cases reported in various hospitals. Low birth weight infants require prolonged and intensive care due to their susceptibility to multiple health complications. Such conditions often trigger varying levels of anxiety among family members. One of the interventions that can be applied to support families during the hospitalization period is Jean Watson’s Theory of Caring. To explore and describe the experiences of families with low birth weight (LBW) infants hospitalized in the NICU, and to examine how Jean Watson’s Caring Theory is implemented by nurses in supporting family adaptation and reducing anxiety during the hospitalization process. A qualitative descriptive phenomenological design was employed. The study involved eight participants selected through purposive sampling. Data were collected through behavioral observations and in-depth interviews with the participants. The findings revealed four main themes of caring consistent with Jean Watson’s perspective: emotional reactions, anxiety responses, caring during treatment, and family expectations. From the experiences of parents of LBW infants in the NICU, four caring themes emerged—emotional reactions, anxiety responses, caring during treatment, and family expectations. These findings were then integrated into the development of a Caring Guideline Book for the care of LBW infants based on Jean Watson’s Theory of Caring. Keywords: Low Birth Weight (LBW), Jean Watson’s Caring Theory, Family Anxiety, Length of Hospitalization.